Uric acid level and kidney function: a cross-sectional study of the Korean national health and nutrition examination survey (2016–2017) - Joo, Hye Jin (Sci Rep, 2020)
Kidney disease is expected to become the fifth leading cause of premature death globally by 2040. Uric acid level is a risk factor for kidney disease. The current study aims to investigate the association between uric acid levels and kidney function in the Korean population. The data of 11,042 participants of the 2016–2017 Korea National Health and Nutrition Examination Survey were analysed. The estimated glomerular filtration rate was calculated using the modification of diet in renal disease formula for Koreans. For each sex, uric acid levels were divided into five subsequent categories of increasing levels (Q1, Q2, Q3, Q4, and hyperuricemia). The association between uric acid level and kidney function was investigated using multiple logistic regression. The results showed that the higher the uric acid levels, the greater the odds of reduced kidney function in both sexes. In men, the adjusted odds ratios (95% confidence intervals) for reduced eGFR comparing the hyperuricemia group to the lowest serum uric acid quartile was 5.55 (3.27–9.44), and in women, the odds ratios (95% confidence intervals) was 7.52 (4.39–12.87). Normal weight or underweight in men and overweight in women, as well as diabetes mellitus, hypertension, and physical inactivity were highly associated with reduced kidney function. Our study revealed a dose–response relationship between uric acid levels and kidney function. Therefore, high uric acid level should be considered as a factor that is potentially related to kidney dysfunction in the Korean population.